Assessment of nutritional status of elderly in rural field practice area of Jhalawar medical college, Jhalawar, India - Yadav, Kamlesh; Dubey, Deepak Kumar; Shukla, Uma Shankar; Sharma, Anubhav (International Journal Of Community Medicine And Public Health, 2023)
Background: Worldwide, the population of elderly people is constantly increasing. Elderly population is at risk of under nutrition due to age related physical, cognitive, functional decline and lack of financial support. Malnutrition contributes to decline in health status, increased utilization of healthcare services and increased mortality. Aim of this study was to assess nutritional status of the elderly by MNA and to find association between nutritional status and socio- demographic profile of elderly. Methods: After ethical approval, a community based cross sectional study was conducted among elderly people residing at Mandawar village, rural field practice area of JMC, Jhalawar during August to October 2022. Complete enumeration technique was used to enrolled participants in study. Door to door household survey was conducted using predesigned questionnaire. Nutritional status was assessed by using standard mini nutritional assessment questionnaire. The data was analyzed through SPSS28.0 (trail version). Results: Out of 287 elderlies, 139 (48.4%) were male and 148 (51.6%) were female. According to MNA, 73 (25.4%) were found malnourished while 119 (41.4%) were at risk of malnutrition and 95 (33.1%) were well nourished. A statistically significant (p<0.05) association was found between nutritional status with increasing age, gender, marital status, education, occupation, morbidity, financial dependance and substance abuse. Conclusions: This study showed that malnutrition has multidimensional background. So, to improve nutritional status of elderly approach should be focus on those who are older, illiterate or low educational status, female gender and financially dependance.